A multiphase micromechanical model for hybrid fiber reinforced concrete considering the aggregate and ITZ effects. (1st July 2016) - Chen, Qing; Zhu, Hehua; Yan, Zhiguo; Ju, J. Woody; Jiang, Zhengwu; Wang, Yaqiong
Highlights: The presented framework can predict the properties of HFRC with the aggregate and ITZ effects. The properties of concrete and FRC can be calculated by the proposed micromechanical models. Different fibers can be considered by the multi-level homogenization scheme step by step. The homogenization sequence for different fibers has little influence on the predicting results. Abstract: Very few micromechanical models are available for hybrid fiber reinforced concrete (HFRC), although it has been widely applied in many structures. To quantitatively predict the effective properties of HFRC with the aggregate and interfacial transition zone (ITZ) effects, a multi-phase micromechanical framework is proposed based on the material's microstructures. In the proposed model, the multi-types of fibers, aggregate, cement paste and ITZ are comprehensively considered. The volume fraction of the ITZ is analytically calculated based on the aggregate grading. Multi-level homogenization schemes are presented to predict the effective properties of HFRC. By utilizing the generalized self-consistent approach, the equivalent matrix composed by the aggregate, cement and the ITZ between them are obtained with the first and second level homogenization procedures. Through adding different types of fibers step by step into the equivalent matrix, the properties of HFRC are reached with the modifications to the Halpin-Tsai model. To demonstrate the feasibility of the proposed micromechanical framework, the predictions herein are compared with the experimental data, the Voigt upper bound and the Reuss lower bound. Finally, the influences of aggregate, ITZ, multi-types of fibers on the properties of HFRC are discussed based on the proposed micromechanical model.